Determination of optimal injection current pattern for multichannel transcranial electrical stimulation without individual MRI using multiple head models - Lee, Sangjun; Park, Jimin; Lee, Chany; Ahn, Jeongyeol; Ryu, Juhyoung; Lee, Sang-Hun; Im, Chang-Hwan (Computer methods and programs in biomedicine, 2024)
•Employment of a mean injection current pattern from multiple head models led to a comparable increment of the stimulation focality of multi-channel tES.•Utilization of the average of the injection currents from multiple head models allowed for a significant decrease of electric fields outside targeted cortical regions.•Employment of mean injection current pattern from multiple head models can focally deliver electric fields to the target without individual MR images. Multichannel transcranial electrical stimulation (tES) is widely used to achieve improved stimulation focality. In the multichannel tES, the injection current pattern is generally determined through an optimization process with a finite element (FE) head model extracted from individual magnetic resonance images (MRIs). Although using an individual head model ensures the best outcome, acquiring MRIs of individual subjects in many practical applications is often difficult. Alternatively, a standard head model can be used to determine the optimal injection current pattern to stimulate a specific target; however, this may result in a relatively inaccurate delivery of stimulation current owing to the difference in individual anatomical structures. To address this issue, we propose a new approach for determining the injection current pattern using multiple head models, which can improve the stimulation focality compared to that achieved with a single standard head model. Twenty FE head models were used to optimize the injection current patterns to stimulate three cortical regions that are widely considered targets for tES. The individual injection current patterns were then averaged to obtain each target's mean injection current pattern. The stimulation focality for each target was then calculated by applying different current patterns (the mean current, individual current, and current from a standard model). Our results showed that the stimulation focality obtained using the mean injection current pattern was significantly higher than that obtained using the injection current pattern from a standard head model. Additionally, our results demonstrated that a minimum of 13 head models are required to determine mean current pattern, allowing for a higher stimulation focality than when using the current from a standard head model. Hence, using multiple head models can provide a viable solution for improving the stimulation efficacy of multichannel tES when individual MRIs are not available.